Modified Laparoscopic Sugarbaker Repair of Parastomal Hernia With a Totally Extraperitoneal Technique - Jiang, Huiyong; Thapa, Dil Momin; Cai, Xiangjun; Ma, Chun; Wang, Mofei (Frontiers in Surgery, 2021)
Purpose: Many patients develop a parastomal hernia within the first 2 years of stoma formation, and even surgical repair is associated with high recurrence rates. An intraperitoneal approach is typically used for the laparoscopic repair of parastomal hernia; it is unknown whether a totally extraperitoneal technique (TEP) is feasible. Here we describe a laparoscopic TEP approach using a modified Sugarbaker method for the repair of parastomal hernia. Methods: Seven patients underwent parastomal hernia repair. The retrograde puncture technique was used to create the extrapneumoperitoneum, and the peritoneum was separated with a laparoscopic TEP approach; the mesh was placed using a modified Sugarbaker technique. Results: All patients had an oncologic etiology for stoma creation. The mean (±SD) size of the hernia defect was 3.1±2.7 cm and the mesh size was 303.4±96.8 cm2. The mean operative time was 195.5±20.7 min and average length of hospital stay after surgery was 4.8±2.1 days. One patient had intraoperative subcutaneous emphysema. The average follow-up time was 8.5±2.7 months; mild pain occurred in 2 patients, 3 experienced seroma formation (with no special treatment required), and 1 had early intestinal obstruction (which was treated with conservative care). There was no hernia recurrence, wound complications, or infections of the surgical site or mesh during follow-up. Conclusion: A laparoscopic TEP technique is technically challenging but feasible. Modified laparoscopic Sugarbaker repair of a parastomal hernia with the TEP technique is safe and effective, although the recurrence rate and late complications require confirmation in more cases with long-term follow-up.